2017
DOI: 10.1186/s13756-017-0239-3
|View full text |Cite
|
Sign up to set email alerts
|

An electronic trigger tool to optimise intravenous to oral antibiotic switch: a controlled, interrupted time series study

Abstract: BackgroundTimely switch from intravenous (iv) antibiotics to oral therapy is a key component of antimicrobial stewardship programs in order to improve patient safety, promote early discharge and reduce costs. We have introduced a time-efficient and easily implementable intervention that relies on a computerized trigger tool, which identifies patients who are candidates for an iv to oral antibiotic switch.MethodsThe intervention was introduced on all internal medicine wards in a teaching hospital. Patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 16 publications
2
21
0
3
Order By: Relevance
“…This could fracture the workability of AMS beyond initial prescribing, with key aspects 'falling between the gaps', particularly in relation to review of antibiotic use. This difficulty has been recognised elsewhere and additional mechanisms to trigger review have been advocated(31,32).Particular tensions were found in our study between AMS principles and heightened concerns around sepsis. Broom and colleagues(33) also found that perceived immediate clinical risks for individuals tend to dominate doctor's prescribing decisions over longer term population health risk.…”
mentioning
confidence: 69%
“…This could fracture the workability of AMS beyond initial prescribing, with key aspects 'falling between the gaps', particularly in relation to review of antibiotic use. This difficulty has been recognised elsewhere and additional mechanisms to trigger review have been advocated(31,32).Particular tensions were found in our study between AMS principles and heightened concerns around sepsis. Broom and colleagues(33) also found that perceived immediate clinical risks for individuals tend to dominate doctor's prescribing decisions over longer term population health risk.…”
mentioning
confidence: 69%
“…Shared decision‐making is a core consideration of the modern clinician, but patients can also be misinformed about inpatient management being somehow superior . This can impair the judicious use of antimicrobials …”
Section: Barriers To Using Po Antibiotics (When Appropriate)mentioning
confidence: 99%
“…This could fracture the workability of AMS beyond initial prescribing, with key aspects 'falling between the gaps', particularly in relation to review of antibiotic use. This difficulty has been recognised elsewhere and additional mechanisms to trigger review have been advocated [31,32]. Particular tensions were found in our study between AMS principles and heightened concerns around sepsis.…”
Section: Discussionmentioning
confidence: 72%